Uncoded transmission in wireless relay networks using deterministic modeling - Schrammar, Nicolas; Skoglund, Mikael (2009 43rd Asilomar Conference on Signals, Systems and Computers, 2009)
We show how communication in the recently proposed deterministic finite field model can be translated into a transmission in the corresponding Gaussian model, using simple uncoded transmission. We find a lower bound on the number of received bits at each node as well as upper and lower bounds on the source-destination rate.